Elfriede Jelineks Theater des (Post-)Politischen Agonistik der Gegenwartsliteratur - Husser, Irene (Gegenwartsliteratur, 2023)
Since the turn of the millennium, there has been a boom in political literature however, the possibilities of political writing in the present must be renegotiated. The challenges of a post-political climate of lack of alternatives are met by Elfriede Jelinek's theatrical work, which - as the field- and discourse-analytical investigation shows - strives to reclaim a democratic culture of the agon.